X-ray diffraction from flight muscle with a headless myosin mutation: implications for interpreting reflection patterns - Iwamoto, Hiroyuki; Trombitás, Károly; Yagi, Naoto; Suggs, Jennifer A.; Bernstein, Sanford I. (Frontiers in Physiology, 2014)
Fruit fly (Drosophila melanogaster) is one of the most useful animal models to study the causes and effects of hereditary diseases because of its rich genetic resources. It is especially suitable for studying myopathies caused by myosin mutations, because specific mutations can be induced to the flight muscle-specific myosin isoform, while leaving other isoforms intact. Here we describe an X-ray-diffraction-based method to evaluate the structural effects of mutations in contractile proteins in Drosophila indirect flight muscle. Specifically, we describe the effect of the headless myosin mutation, Mhc10-Y97, in which the motor domain of the myosin head is deleted, on the X-ray diffraction pattern. The loss of general integrity of the filament lattice is evident from the pattern. A striking observation, however, is the prominent meridional reflection at d = 14.5 nm, a hallmark for the regularity of the myosin-containing thick filament. This reflection has long been considered to arise mainly from the myosin head, but taking the 6th actin layer line reflection as an internal control, the 14.5-nm reflection is even stronger than that of wild-type muscle. We confirmed these results via electron microscopy, wherein image analysis revealed structures with a similar periodicity. These observations have major implications on the interpretation of myosin-based reflections.